“Empty Breast" and digital oral stimulation: a comparison between techniques in oral dietary transition in preterm (Research, Society and Development, 2022)
Purpose: This study intent to investigate the effectiveness of the "Empty Breast" technique, in relation to the standard digital oral stimulation technique, and examine the amount of time of use of orogastric tube, length of hospitalization, and breastfeeding prevalence at hospital discharge. Methods: It is an intervention study with prospective, longitudinal, clinical-type data collection, comparing two techniques used to transition enteral nutrition to oral nutrition in preterm. The participants were divided into two groups, 17 being the control group stimulated with the non-nutritive sucking technique in gloved finger , 15 experimental group stimulated by the “empty breast” suction technique. Data were analyzed using descriptive and inferential statistics. The level of significance adopted for the inferential statistical analyzes was 5% (p